Meninjau Nilai Keadilan yang Terkandung dalam Jarimah Qishas dan Diyat - Namira Khaulani; Nadya Oktaviani Rahma; Puja Maulana; Muhamad Rafly Alamsyah; Deden Najmudin (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
Allah SWT has explicitly commanded in the Quran, particularly in Surah An-Nisa, verse 58, that laws among humanity should be established with utmost justice. In the field of fiqh jinayah, these laws not only serve as tools for enforcing criminal justice but also reflect principles of justice derived from the Quran and Hadith. This research aims to investigate the underlying values of justice in the punishments of qishas and diyat as part of fiqh jinayah, and to comprehend their significance in resolving conflicts arising from violence or killings ordained by Allah SWT. The qualitative descriptive approach, utilizing literature review as the research method, is employed in crafting this article. The study concludes that the concepts of qishas and diyat demonstrate a sense of reconciliation in the conflict resolution process involving perpetrators, victims, and their families, especially with the implementation of diyat payments or full forgiveness. Consequently, the involvement of the victims' families plays a crucial role in determining the form of justice, serving as a counterbalance to the primary objectives of the Islamic justice system. In essence, the principles of qishas and diyat not only uphold justice but also promote reconciliation in the pursuit of a fair legal system.